LITERASI KEUANGAN DAN PERILAKU PENGELOLAAN KEUANGAN UMKM TERHADAP PERAN INKUBATOR BISNIS DI KOTA PALU - Saharuddin, Muhammad Fahmi; Munawarah, Munawarah; Surraya, Surraya; Rianty, Cici (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The aim of this research is to analyze the influence of financial literacy and financial management behavior of MSMEs on the role of business incubators in Palu City. The research method used is a quantitative approach. The population and sample in this research were 52 MSMEs with 40 MSME respondents assisted by business incubators using purpose sampling techniques. The data analysis technique uses multiple linear regression analysis. The research results show that financial literacy and financial management behavior simultaneously have a significant effect on the role of business incubators with a significance level of 7,588 < 0.002. However, partially the financial literacy variable with a significant level of 1,088 < 0.283 and financial management behavior with a significant level of 1,499 < 0.142, shows an insignificant influence on the role of business incubators.